APAKAH MEKANISME GCG DAN UKURAN PERUSAHAAN BERDAMPAK PADA HARGA SAHAM? - Nurul Karlina Surya Wijaya; Annisa Fatimah; Mohammad Arief Setiawan (Jurnal Akuntansi Indonesia, 2020)
In this study good corporate governance indicators consist of board of commissioners, independent commissioners and managerial ownership The population of this research were the mining companies listed in Indonesia Stock Exchange during the period 2012-2017. Based on the criteria, there were 5 companies. The methods of data analysis that used in this study was quantitative method with multiple linear regression analysis. The results of this research were the Board of Commissioners has a significant effect towards stock prices partially. While the independent Commissioner, managerial ownership and firm size have not significant effect towards stock prices. However, the Board of Commissioners, independent Commissioner, managerial ownership and firm size have significant effect towards the stock price simultaneously.